2019
DOI: 10.1155/2019/6327041
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Primary and Systemic Metastatic Intraocular Lymphomas in Spanish Patients

Abstract: Objectives To describe and compare clinical findings in different subtypes of biopsy-proven intraocular lymphomas (IOLs). Design Retrospective, observational case series. Methods The clinical and pathologic features in IOLs at the Hospital Clinic of Barcelona from 1995 to 2018 were retrospectively studied. Results Twenty-one patients, 12 men (57%), median age 60 (interquartile range, IQR: 18 years), and a median follow-up of 30 (IQR 60) months were included. Eleven patients had primary vitreo-retinal lymphoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…In case of orbital infiltration (proptosis, ophthalmoplegia, pupillary disfunction, low visual acuity, among others), the risk of metastasis is high (Llorenç et al. 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In case of orbital infiltration (proptosis, ophthalmoplegia, pupillary disfunction, low visual acuity, among others), the risk of metastasis is high (Llorenç et al. 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In the immunosuppressed, it is not unusual for VRL to present at a younger age. Some authors have reported a slight male gender predilection, with the male/female ratio of 1.2-1.7:1 [53], while more recent publications found a slight female predominance [7,40,52,54].…”
Section: Epidemiology and Pathogenesismentioning
confidence: 95%
“…Occasionally patients may present with large clumps of malignant cells on the corneal endothelium, mimicking granulomatous KP (Figure 7b). Corneal edema, pseudohypopyon [54,74] and pupil distortion may be present but are not common [65]. As the anterior segment inflammation is minimal, photophobia, pain and redness are uncommon symptoms [6].…”
mentioning
confidence: 99%
“…PVRL most commonly represents non-Hodgkin's lymphoma (NHL), and 90% of cases have di use large B-cell lymphoma (DLBCL) [3]. e clinical features of PVRL are nonspeci c, including the presence of large, nonclumped vitreous cells and white-yellow subretinal deposits associated with solid retinal pigment epithelium (RPE) detachments [4], making it one of the most common masquerade syndromes [5,6].…”
Section: Introductionmentioning
confidence: 99%